Pengaruh Manajemen Modal Kerja Terhadap Kinerja Keuangan Pada Perusahaan Jasa Sektor Property Dan Real Estate Yang Terdaftar Dalam Indeks Saham Syariah - Thiyas Fitri Ayu Adheansyah; Youdhi Prayogo; Muthmainnah Muthmainnah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
As time went by, many changes were discovered from outside the company. Due to rapid changes in a company's external reach, companies must also be able to adapt and compete with other companies. Sufficient working capital allows the company to operate as economically as possible, and the company does not face difficulties or threats that may arise due to crises or economic chaos. The aim of this research is to determine the effect of working capital management on the financial performance of property and real estate companies listed in the sharia stock index. The number of samples in this research was 20 companies for the 2020-2022 period after sampling using the purposive sampling method. Panel data analysis is used as a data analysis technique. The partial research results show that there is no effect of working capital management on financial performance, but simultaneously working capital management has an effect on the company's financial performance by 11.9%. When testing classical assumptions with a normal distribution, heteroscedasticity and multicollinearity do not occur.